Analisis Kadar Protein dan Pertumbuhan Biomassa dari Chlorella sp. dan Nannochloropsis sp. pada Kultur Tunggal dan Campuran yang Diperoleh dari Remediasi Anaerobically Digested Dairy Manure Wastewater (ADDMW) Menggunakan Bioreaktor Open Raceway Pond: Biomass and Protein Production of Chlorella spp. and Nannochloropsis spp. in Single and Mixed Cultures on Anaerobically Digested Dairy Wastewater - Muhammad Farhan Aidira; Taufikurahman; Lili Melani (Jurnal Sumberdaya Hayati, 2026)
Microalgae are known for their ability to produce protein and reduce certain pollutant levels. One of the main challenges in microalgae cultivation is the provision of suitable synthetic growth media. Anaerobically Digested Dairy Manure Wastewater (ADDMW) has potential as an alternative growth medium due to its relatively high nutrient content. This study aims to analyze the effect of ADDMW-based cultivation on the growth rate, biomass production, and protein production of Chlorella spp. and Nannochloropsis spp., cultivated both in monoculture and mixed culture systems using an open raceway pond bioreactor. Cultivation was carried out using Chlorella spp. and Nannochloropsis spp. with an initial volume ratio of 1:1 (v/v) over a 7-day period, and the ADDMW wastewater was diluted 25 times prior to use. The highest specific growth rate, biomass yield, and biomass productivity were observed in the mixed culture, with values of 1.47 day⁻¹, 0.95 g·L⁻¹, and 0.28 g·L⁻¹ day⁻¹, respectively. The highest protein content was also obtained from the mixed culture, reaching 56.25% of dry biomass, whereas the protein content in monocultures of Chlorella spp. and Nannochloropsis spp. was 40.42% and 40.11%, respectively.